Potensi Kriminalitas dan Strategi Penanggulangannya di Wilayah Hukum Kepolisian Daerah Nusa Tenggara Timur - Yohana Yosiana Djara Dima; Aksi Sinurat; Karolus Kopong Medan (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
This study is motivated by the increasing dynamics of criminal activity within the jurisdiction of the East Nusa Tenggara Regional Police (Polda NTT), characterized by regional variations and complex causal factors. Conventional crimes such as assault, theft, and mob violence dominate the crime landscape and significantly affect social stability. The purpose of this research is to analyze the patterns, causes, and crime control strategies implemented by Polda NTT in maintaining public security and order. The study employs an empirical legal approach using a mixed-methods design, combining quantitative analysis of crime statistics with qualitative interviews involving police officers. Data were obtained from the Directorate of General Criminal Investigation (Ditreskrimum) of Polda NTT and cover all police jurisdictions, including one city police department and twenty-one district police offices. Findings reveal that crime rates in NTT are strongly influenced by social, economic, cultural, and geographical factors. The most prevalent crimes include assault, ordinary theft, traffic accidents, and mob violence. Major contributing factors consist of a local culture of violence, alcohol consumption, economic hardship, and low legal literacy. Polda NTT’s strategies involve preventive measures (routine patrols and public legal education), repressive actions (law enforcement and offender guidance), and humanistic approaches such as the Jumat Curhat program, which facilitates direct dialogue with the community.